The Council Estate and "Being Placed": Everyday Resistances to the Stigmatization of Community. Issue 4 (7th August 2020) - Leaney, Sarah
ABSTRACT: Building upon contemporary analyses of the interconnections between stigmatized places and identity formation, this paper explores processes of place-based identity formation on a British council estate. Connecting post-structural theorisations of identity and space, the paper explores the tensions between structure and agency implicit within theorisations of place-based identity as a community. Conceptualising the entanglement of structure and agency in place making as "being placed", this paper offers an analysis of contradictions inherent in a structurally located agency. Founded upon ethnographic research of the material and cultural conditions of "being placed" on The Estate, the paper explores everyday resistances to place-based identity and the stigmatization of community.